Ferritin Conjugates With Multiple Clickable Amino Acids Encoded by C-Terminal Engineered Pyrrolysyl-tRNA Synthetase - Wang, Yi-Hui; Jian, Mu-Lung; Chen, Pei-Jung; Tsou, Jo-Chu; Truong, Le P.; Wang, Yane-Shih (Frontiers in Chemistry, 2021)
This study reports the application of expanding genetic code in developing protein cage-based delivery systems. The evolved Methanosarcina mazei pyrrolysyl-tRNA synthetase (PylRS)•tRNA_Pyl pairs derived from directed evolution are examined to probe their recognition for para-substituted phenylalanine analogs. The evolved MmPylRS, AzFRS, harboring a wide range of substrates, is further engineered at the C-terminal region into another variant, AzFRS-MS. AzFRS-MS shows the elevated sfGFP protein amount up to 10 TAG stop codons suppression when charging p-azido-L-phenylalanine (AzF, 4), which allows the occurrence of click chemistry. Since protein nanocages used as drug delivery systems that encompass multiple drugs through a site-specific loading approach remains largely unexplored, as a proof-of-concept, the application of AzFRS-MS for the site-specific incorporation of AzF on human heavy chain ferritin (Ftn) is developed. The Ftn-4 conjugate is shown to be able to load multiple fluorescence dyes or a therapeutic agent, doxorubicin (Dox), through the strain-promoted azide-alkyne cycloaddition (SPAAC) click reaction. Aiming to selectively target Her2+ breast cancer cells, Ftn-4-DOX conjugates fused with a HER2 receptor recognition peptide, anti-Her2/neu peptide (AHNP), is developed and demonstrated to be able to deliver Dox into the cell and to prolong the drug release. This work presents another application of evolved MmPylRS systems, whose potential in developing a variety of protein conjugates is noteworthy.